(untitled) - Clovis Monteiro BRAMANTE; Marcia Magro KATO; Gerson Francisco de ASSIS; Marco Antonio Hungaro DUARTE; Norberti BERNARDINELI; Ivaldo Gomes de MORAES; Roberto Brandão GARCIA; Ronald ORDINOLA-ZAPATA; Alexandre Silva BRAMANTE (University of São Paulo, 2013)
ObjectiveTo evaluate the biocompatibility and the setting time of Portland cement clinker with or without 2% or 5% calcium sulfate and MTA-CPM.Material and MethodsTwenty-four mice (Rattus norvegicus) received subcutaneously polyethylene tubes filled with Portland cement clinker with or without 2% or 5% calcium sulfate and MTA. After 15, 30 and 60 days of implantation, the animals were killed and specimens were prepared for microscopic analysis. For evaluation of the setting time, each material was analyzed using Gilmore needles weighing 113.5 g and 456.5 g, according to the ASTM specification Number C266-08 guideline. Data were analyzed by ANOVA and Tukey's test for setting time and Kruskal-Wallis and Dunn test for biocompatibility at 5% significance level.ResultsHistologic observation showed no statistically significant difference of biocompatibility (p>0.05) among the materials in the subcutaneous tissues. For the setting time, clinker without calcium sulfate showed the shortest initial and final setting times (6.18 s/21.48 s), followed by clinker with 2% calcium sulfate (9.22 s/25.33 s), clinker with 5% calcium sulfate (10.06 s/42.46 s) and MTA (15.01 s/42.46 s).ConclusionsAll the tested materials showed biocompatibility and the calcium sulfate absence shortened the initial and final setting times of the white Portland cement clinker.